To subtract 1/2(z+4)−3(1/4z+1), we need to distribute the negative sign to both terms inside the parentheses:
1/2(z+4) = 1/2z + 2
3(1/4z + 1) = 3/4z + 3
Now, subtract the two terms:
(1/2z + 2) - (3/4z + 3)
To combine fractions with different denominators, we need to find a common denominator. In this case, the common denominator is 4.
(1/2z + 2) - (3/4z + 3) = (2/4z + 2) - (3/4z + 3)
Next, combine like terms:
(2/4z + 2) - (3/4z + 3) = (2 - 3)/4z + (2 - 3) = -1/4z - 1
Therefore, the final answer in fraction form is -1/4z - 1.
Subtract 1/2(z+4)−3(1/4z+1) . Use fractions in final form. corerect answer
1 answer